Cloud native intelligent operation and maintenance technology - Long XUE; Gang LU; Qi ZHOU; Huiyan ZHANG; Tingjun WAN (Dianxin kexue)
Relying on the advantages of simple and fast applications,easy deployment of applications,and on-demand scaling of running applications,cloud native technology has been rapidly promoted.However,with the application of cloud native,the system architecture has become more complex and the scale of resources has become larger,and there is an urgent need for more intelligent operation and maintenance.Using intelligent operation and maintenance can better assist cloud-native application development,reduce operation and maintenance costs,and improve service quality.The application scenarios,key points,classic practices and existing problems of intelligent operation and maintenance were analyzed,and a cloud-native intelligent operation and maintenance architecture were proposed,and the main principles of the three scenarios:the trend prediction,data anomaly detection and fault location diagnosing in the core service algorithm platform were introduced in detail,and finally the future of intelligent operation and maintenance were looked forward.